Modeling a Heterogeneous Embedded System in Coloured Petri Nets - Huafeng Zhang; Hehua Zhang; Ming Gu; Jiaguang Sun (Journal of Applied Mathematics)
Embedded devices are everywhere now and, unlike personal computers, their systems differ in implementation languages and behaviors. Interactions of different devices require programmers to master programming paradigms in all related languages. So, a defect may occur if differences in systems' behaviors are ignored. In this paper, a heterogeneous system which is composed of two subsystems is introduced and we point out a potential defect in this system caused by an interface mismatch. Then, a state based approach is applied to verify our analysis of the system.